Regulating cell-cultured animal material for food systems transformation: current approaches and future directions. Issue 1 (2nd January 2021) - Johnson, Hope
ABSTRACT: Proponents and developers of cell-cultured animal material (i.e. lab-grown meat) vest the innovation with the capacity to transform food systems by replacing, or significantly reducing, intensive use of animals in food systems. This article argues that cell-cultured animal material reflects lock-in to the incumbent, productivist regime for agricultural innovation. First, the article positions cell-cultured animal material as broadly consistent with the paradigm underlying intensive animal agriculture and related innovations. Secondly, it 2 explores how intellectual property has become the regulation-by-default of cell-cultured animal material reinforcing well-known limits of intellectual property rights to transform agricultural systems. Thirdly, it considers the broader regulatory context for cell-cultured animal material. The article shows how the claims by proponents and the responses from incumbent industry actors have narrowed regulatory responses preventing regulators from engaging with deeper questions about, and pathways for, food systems transformation; and, it concludes by briefly considering an alternate regulatory approach to cell-cultured animal material.